Analisis Semiotik Pesan Dakwah dalam Akun Tiktok @huseinjafar - Muhammad Hafizh Fachry Aldira; Khuza'i, Rodliyah (UNISBA Press, 2024)
Abstract. Tiktok is a social networking application in which users can create, edit and share short videos. The tiktok application has many opportunities in its utilization. Not a few content creators share their videos to educate the audience. One of the educational content creators of TikTok also provides benefits in preaching to the public, namely Habib Husein Ja'far with the account name @huseinjafar. This research focuses on Habib Jafar's Dakwah messages in his TikTok account@huseinjafar which some people commented negatively. The purpose of this study is to know the representamen (signs), objects and interpretants on the account@huseinjafar based on Charles Sanders Peirce's semiotic theory and to find out da'wah messages in tiktok videos on accounts@huseinjafar.This research uses a type of qualitative research with descriptive methods, data collection techniques with observation and documentation. The results of this study are in the semiotic analysis of several tiktok videos@huseinjafar shows representamen (signs), objects, and interpretants based on Charles Sanders Peirce's semiotic theory. The results of research on da'wah messages in tiktok videos on accounts@huseinjafarcontains the preaching message of Creed, Sharia and Ethics. Abstrak. Tiktok merupakan sebuah aplikasi jejaring sosial dalam penggunaanya dapat membuat, mengedit, dan berbagi video pendek. Aplikasi tiktok memiliki banyak peluang dalam pemanfaatannya. Tidak sedikit konten kreator yang membagikan videonya untuk mengedukasi penonton. Salah satu konten kreator tiktok yang mengedukasi juga memberi manfaat dalam berdakwah kepada khalayak yakni Habib Husein Ja’far dengan nama akun @huseinjafar. Penelitian ini berfokus pada Pesan Dakwah Habib Jafar dalam akun tiktok @huseinjafar yang segelintir orang berkomentar negatif. Tujuan penelitian ini adalah mengetahui representamen (tanda), objek dan interpretant pada akun @huseinjafar berdasarkan teori semiotika Charles Sanders Peirce dan untuk mengetahui pesan dakwah dalam video tiktok pada akun @huseinjafar. Penelitian ini menggunakan jenis penelitian kualitatif dengan metode deskriptif, teknik pengumpulan data dengan observasi dan dokumentasi. Hasil penelitian ini dalam analisis semiotik beberapa video tiktok @huseinjafar menunjukkan representamen (tanda), objek, dan interpretant berdasarkan teori semiotika Charles Sanders Peirce. Hasil penelitian pesan dakwah dalam video tiktok pada akun @huseinjafar mengandung pesan dakwah Akidah, Syariat dan Akhlak.